Menumbuhkan Karakter Moderasi Beragama Islam Sejak Dini di Lingkungan Keluarga untuk Masa Depan Anak-Anak Indonesia - Musya'Adah, Umi; Istifhama, Lia (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
Families must be able to guard their children so that they stay on a moderate path in Islam, as parents who have the first and foremost role in the family. Parents are able to produce children to become experts in various fields, but if their children's understanding, especially actions, when they grow up, they will have excessive religious understanding, their religious ways are deviant, and often disturb many people, then all the skills and abilities they have owned by our children would be meaningless.Children in their family environment must always be strengthened and instilled from an early age the character of Islamic moderation, so that when the child is an adult, when the child is separated from his parents, for example in the school environment, the child already has a foundation. strong and difficult to be influenced by things that are radically charged and exaggerated. Several bombing cases that occurred in Indonesia, after being investigated, it turned out that the perpetrators were Muslim. This incident greatly tarnished Islam as a religion of peace, as a religion that is Rahmatal lil alamin. There is nothing wrong with the teachings of Islam. However, to this day, the way to understand Islam for each individual must always be maintained. Religious moderation is present and has the aim of maintaining religious harmony.